Bonus payments and fund managers' behavior: Trans-Atlantic evidence - Thomas P. Gehrig; Torben Lütje; Lukas Menkhoff (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2008)
This questionnaire survey of fund managers in the United States, Germany and Switzerland documents a distinctly positive influence of bonus payments on investment behavior on both sides of the Atlantic. Higher bonus payments are significantly related to higher working effort but not to risk taking. They also seem to induce fund managers to rely more on fundamental information. Findings within regions are confirmed by Trans-Atlantic evidence as US fund managers receive larger bonuses but also show the effects to a higher degree. The effects documented are stronger for relative than for absolute performance assessment.
Keywords: G23; G14; 330; Fund managers; incentives; fundamental information; Investmentfonds; Führungskräfte; Vergütungssystem; Leistungsanreiz; Betriebliche Investitionspolitik; Risikopräferenz; Vergleich; USA; Deutschland; Schweiz